PELATIHAN BAHASA INGGRIS BAGI PERANGKAT DESA DAN STAF KANTOR PERBEKEL PERERENAN - Ida Bagus Gde Nova Winarta; Putu Gede Budiartha; I Made Yogi Marantika; I Putu Aris Sucipta; Wayan Nurita (Fakultas Bahasa Asing, 2025)
In the era of globalization, English language proficiency has become an essential skill, especially for village officials and village office staff who frequently interact with outsiders, including foreign tourists. Pererenan Village, located on the main tourism route in Bali, faces challenges in improving the international communication capacity of its village officials. To overcome this obstacle, an English language training program was conducted as part of the community service activities. The program included theoretical learning, group discussions, and hands-on practice in real situations, aiming to improve basic communication competencies in English. The results of this activity showed a significant improvement in the participants' English language skills, which improved the quality of public services in the village and increased the competitiveness of Pererenan Village as a tourist destination. This community service not only contributes to the development of human resources but also strengthens the relationship between the university and the local community and makes a tangible contribution to facing the challenges of globalization and advancing Pererenan Village on the international stage.